Batuh Narit Arur Bilit of Pa’ Umor : A Visual Analysis onto a Carved Stone from the Megalithic Monuments of the Kelabit Highlands - Rafee, Y.M; Awangko Hamdan, Awang Arshad; Sylvester Wielding, Jussem; Hishamuddin, Siri; Bala, P.; Maying, D.; Aman Leong, S.N. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper seeks to investigate on the Kelabit’s material culture based on a visual archaeological study of the megalithic stone, particularly the carved stone known as Batuh Narit Arur Bilit, from the district of Pa’ Umor in Bario, Sarawak, Malaysia. The primary focus of this paper is to advance knowledge within the practice, especially in visual art research, and how it can be used as digital content to promote eco-tourism in the rural area. Previously, there was a lack of techniques that can be used as an example of how visual art can be used to explore other disciplines such as anthropology. Thus, this study will highlight several issues pertaining to the visual documentation process of the megalith, notably on the relation of the symbol and drawing carved on the surface of the stone. By using empirical research, the biography of the monument will be explored via experiential learning and visual analysis, especially in considering our sensory with practical experience. These findings are the result of visual recording practices such as drawing, photography, and video as well as site observations, with the highlight of the discovery of the long-lost stone carvings. What started as an unintentional discovery has evolved into a rich visual study of the cultural narratives and has developed as an identity that also has a historical impact and cultural content for the eco-tourism sector in the Kelabit society.